2019
DOI: 10.1039/c9cc02990g
|View full text |Cite
|
Sign up to set email alerts
|

Co-crystal LiCl·(H3C3N3O3): a promising solar-blind nonlinear optical crystal with giant nonlinearity from coplanar π-conjugated groups

Abstract: Co-crystal LiCl·(H3C3N3O3) with the largest SHG coefficient among all solar-blind nonlinear optical crystals was studied by first principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 30 publications
0
62
0
Order By: Relevance
“…The majority of the non-hydro-cyanurates known to date show γ = 0°with only two exceptions, LiSrC 3 N 3 O 3 (22, Table 1) and SrC 3 N 3 O 3 OH (23, Table 1). [11][12][13][14]20,25,26 In addition, the cocrystal trihydro-cyanurate, LiCl•H 3 C 3 N 3 O 3 , 27 is synthesized, but no single-crystal data is available. Regarding these two types of compounds, because of the lack of Δn data, their Δn−γ correlation cannot be discussed herein.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the non-hydro-cyanurates known to date show γ = 0°with only two exceptions, LiSrC 3 N 3 O 3 (22, Table 1) and SrC 3 N 3 O 3 OH (23, Table 1). [11][12][13][14]20,25,26 In addition, the cocrystal trihydro-cyanurate, LiCl•H 3 C 3 N 3 O 3 , 27 is synthesized, but no single-crystal data is available. Regarding these two types of compounds, because of the lack of Δn data, their Δn−γ correlation cannot be discussed herein.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With one more H atom per ring in the dihydro-cyanurates, the population of the N atom in VBM is dramatically suppressed in comparison with that in hydro-cyanurates (Figure S6). These results agree well with those reported in refs and . Consequently, the CY rings are the major source that contributes mainly to the bands around the E F .…”
Section: Resultsmentioning
confidence: 99%
“…9. 50,51 The structure is characterized by graphite-like quasi-2D infinite layers composed of [H 3 C 3 N 3 O 3 ] units connected by a [LiO 3 Cl] tetrahedron (Fig. 9b and c Pb 2 BO 3 Br and Pb 2 BO 3 I are isomorphic to this compound, which are not discussed here.…”
Section: Uv Transparent Cyanurates With Planar [H X C 3 N 3 O 3 ] Groupsmentioning
confidence: 99%
“…Fei Liang et al [88] investigated already reported Co-crystal LiCl(H 3 C 3 N 3 O 3 ) LCHCY 107 by using first-principles studies to analyse its suitability in Solar-bind lasers. LCHCY crystal crystallized in polar space group R3 m. The grown crystal structure resembles graphite-like quasi-two-dimensional infinite layers made up of (H 3 C 3 N 3 O 3 ) molecules attached by (LiO 3 Cl) tetrahedral.…”
Section: Cyanurates Seriesmentioning
confidence: 99%
“…Fei Liang et al [88] . investigated already reported Co‐crystal LiCl(H 3 C 3 N 3 O 3 ) LCHCY 107 by using first‐principles studies to analyse its suitability in Solar‐ bind lasers.…”
Section: Introductionmentioning
confidence: 99%